A Comparison of the Effectiveness of the Combined Cognitive–Emotional Reconstruction Package for Infertile Women and Unified Transdiagnostic Couple Therapy on Emotion Regulation and Affective Capital - Ahmadi, Sanaz; Golparvar, Mohsen; Yousefi , Zahra (Mental Health and Lifestyle Journal, 2026)
Infertility is one of the most stressful and distressing experiences in marital life and can profoundly influence the emotional conditions and relationship quality of couples. The purpose of the present study was to compare the effectiveness of the combined cognitive–emotional reconstruction couple intervention with unified transdiagnostic couple therapy on emotion regulation and affective capital in infertile women. The study employed a quasi-experimental design with pretest–posttest and a two-month follow-up, including a control group. The statistical population consisted of infertile women who sought services at infertility centers in Isfahan during the winter of 2024. From this population, 60 individuals were selected through purposive sampling and randomly assigned to three groups of 20 participants each. The combined cognitive–emotional reconstruction couple treatment and unified transdiagnostic couple therapy were administered over ten 60-minute sessions. The research instruments included the Cognitive Emotion Regulation Questionnaire (Gross & John, 2003) and the Affective Capital Scale (Golparvar, 2018). Data were analyzed using repeated-measures ANOVA and Bonferroni post hoc tests in SPSS version 26. The results indicated that both therapeutic approaches, when compared with the control group, significantly improved emotion regulation and increased affective capital (p < .01). In comparing the two therapeutic methods, cognitive–emotional reconstruction showed significantly greater effectiveness than unified transdiagnostic couple therapy in the reappraisal component of emotion regulation and in affective capital; however, in the emotional suppression component of emotion regulation, both approaches demonstrated similar levels of effectiveness